Histone lactylation mediated by Fam172a in POMC neurons regulates energy balance - Zhuo Chen; Baocheng Wan; Hong Zhang; Lina Zhang; Rong Zhang; Lianxi Li; Yi Zhang; Cheng Hu (Nature Communications)
Abstract Glycolysis-derived lactate was identified as substrate for histone lactylation, which has been regarded as a significant role in transcriptional regulation in many tissues. However, the role of histone lactylation in the metabolic center, the hypothalamus, is still unknown. Here, we show that hypothalamic pro-opiomelanocortin (POMC) neuron-specific deletion of family with sequence similarity 172, member A (Fam172a) can increase histone lactylation and protect mice against diet-induced obesity (DIO) and related metabolic disorders. Conversely, overexpression of Fam172a in POMC neurons led to an obesity-like phenotype. Using RNA-seq and CUT&Tag chromatin profiling analyzes, we find that knockdown of Fam172a activates the glycolytic process and increases peptidylglycine α-amidating monooxygenase (PAM), which affects the synthesis of α-MSH, via H4K12la (histone lactylation). In addition, pharmacological inhibition of lactate production clearly abrogates the anti-obesity effect of PFKO (POMC-Cre, Fam172a loxP/loxP , POMC neurons Fam172a knockout). These findings highlight the importance of Fam172a and lactate in the development of obesity and our results mainly concern male mice.